2018
DOI: 10.1038/s41421-018-0067-5
|View full text |Cite
|
Sign up to set email alerts
|

A new role of anterograde motor Kif5b in facilitating large clathrin-coated vesicle mediated endocytosis via regulating clathrin uncoating

Abstract: Kif5b-driven anterograde transport and clathrin-mediated endocytosis (CME) are responsible for opposite intracellular trafficking, contributing to plasma membrane homeostasis. However, whether and how the two trafficking processes coordinate remain unclear. Here, we show that Kif5b directly interacts with clathrin heavy chain (CHC) at a region close to that for uncoating catalyst (Hsc70) and preferentially localizes on relatively large clathrin-coated vesicles (CCVs). Uncoating in vitro is decreased for CCVs f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 65 publications
1
5
0
Order By: Relevance
“…All mice were housed in a specific pathogen-free facility at LAU, HKU, under a 12 h/12 h light/dark cycle, and provided with food and water. The heterozygous KIF5B knockout (KIF5B +/− ) mouse line was generated by Prof. Huang’s group ( Ni et al, 2018 ; Lin et al, 2019 ). The KIF5B +/− mice were crossed with P301S mice to obtain the experimental cohort of P301S +/− and P301S +/− ,KIF5B +/− in C57B6 background The genotype of all animals was confirmed by polymerase chain reaction (PCR).…”
Section: Methodsmentioning
confidence: 99%
“…All mice were housed in a specific pathogen-free facility at LAU, HKU, under a 12 h/12 h light/dark cycle, and provided with food and water. The heterozygous KIF5B knockout (KIF5B +/− ) mouse line was generated by Prof. Huang’s group ( Ni et al, 2018 ; Lin et al, 2019 ). The KIF5B +/− mice were crossed with P301S mice to obtain the experimental cohort of P301S +/− and P301S +/− ,KIF5B +/− in C57B6 background The genotype of all animals was confirmed by polymerase chain reaction (PCR).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, we found that CHC could also directly bind, albeit weakly, to kinesin-1 via its tail domain (KIF5B aa 808-963) (Figure 1F). This interaction was also reported in a recent study describing a role of direct binding by the kinesin-1 KIF5B in the uncoating of clathrin-coated vesicles (Ni et al, 2018). Altogether, we have identified clathrin as a novel MAP7D2-specific interaction partner and showed that these proteins can form a triple complex together with kinesin-1.…”
Section: Map7d2 But Not the Other Mammalian Map7 Family Members Can Associate With Clathrinsupporting
confidence: 87%
“…Here, we show that MAP7D2 has the unique property of binding and recruiting clathrin to MTs and that this MAP is important for the localization of clathrin in the axon. Kinesin-1 can also bind clathrin directly (Ni et al, 2018); we therefore hypothesize that MAP7D2 has a dual role in steering kinesin-1 transport and loading cargo onto the motor. Future experiments may resolve how large cytosolic protein complexes such as clathrin and neurofilaments are sorted and transported, and how specific MAPs can contribute to this process in a spatially regulated manner.…”
Section: Discussionmentioning
confidence: 97%
“…To confirm whether EGFP was transferred from astrocytes to neurons via exosomes, we inject GW4869 in the same site injected with AAV- GFAP -Cre-EGFP and examine the dissemination of EGFP. Previous studies demonstrated that 10–20 μM GW4869 could decrease more than 70% exosomes released from neurons 28 and astrocytes 29 . Here we injected 1 μl of 80 μM GW4869 in the cortex to inhibit exosome formation thoroughly.…”
Section: Resultsmentioning
confidence: 96%